Ordinances of the Borough of Shamokin, Pa., at 71-72, An Ordinance Regulating the Storage of Coal, Oil, Benzene and Other Inflammable Oils and Regulating the Hauling and Storage of Gun Powder and other Explosives in the Borough of Shamokin, § 3 (1896) - (:unkn) unknown (My University, 1896)
That no person shall convey or cause to be conveyed through any of the streets, lanes or alleys of the Borough in any cart, wagon or other vehicle, at any one time, any greater quantity of gun powder, blasting powder, or other explosives than twenty five pounds without a sheet of canvass under, around and over the same sufficient to prevent it from being scattered from the said cart, wagon or vehicle, or being ignited by sparks or otherwise under the penalty of forfeiture of the said gun powder, blasting powder or other explosive, and for every such offense the person so offending upon conviction thereof before the Chief Burgess or any Justice of the Peace within the Borough shall pay a fine of not less than One Dollar nor more than Ten Dollars to be collected as penalties of like amount are not by law collectible.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER